CORPORATE GOVERNANCE DISCLOSURE IN THE EXISTENCE OF OWNERSHIP STRUCTURE AND GROWTH OPPORTUNITIES - Melinda Lydia Nelwan (Jurnal Keuangan dan Perbankan, 2017)
This study examines whether ownership structure which was divided into blockholderownership, managerial ownership, and public ownership had influence on corporategovernance disclosure, and whether growth opportunities moderate that influence. Studiesin this area mostly examined the role of ownership structure on corporate financialdisclosure or public announcements conducted in the context of different countries andin more regulated industries in Indonesia. The scope of this study was manufacturingcompanies listed on the Indonesian Stock Exchange for the period of 2013. The resultsshowed that between the ownership structures only blockholder ownership had a negativeand significant influence on the corporate governance disclosure. Being the largestshareholders, blockholders might have better access on the inside information whichmade them better informed relative to other shareholders, thus arguably might desire lessdisclosure. The results also showed that the interaction variable between managerialownership and growth opportunities was negative and significant. This indicates that ina growing company where the managerial ownership increases, the management wouldtend to reduce the corporate governance information they provided to the stakeholders.